PENGARUH PENGGUNAAN GADGET TERHADAP INTERAKSI SOSIAL ANAK USIA SD - Nadhifa Salsabila Joshanda; Adrias, Adrias; Aissy Putri Zulkarnaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the impact of gadget use on social interactions of children at elementary school age. Around us, we often see that children at this age have difficulty in social interactions, both with peers and with their surroundings. This phenomenon shows that many children are more focused on gadgets and tend to do activities alone, thus losing the opportunity to interact with others. The method used in this study is the Systematic Literature Review (SLR), which aims to study, disseminate, identify, and interpret various studies related to this phenomenon. With the SLR approach, this study succeeded in analyzing and identifying journals systematically. Data were obtained by searching for articles from various online journals through Google Scholar. The results of the study show that excessive use of gadgets, especially without parental supervision, can hinder the process of children's social interactions. Their attention is often diverted from the surrounding environment to gadgets, which in turn results in decreased social interactions with people around them.